SARS-CoV-2 genomic surveillance using rapid point of care COVID-19 antigen tests at public test sites in California - Foote, Eric M.; Bouchard, Ellen L.; Acharya, Charlotte B.; Baylis, Elizabeth F.; Bell, John M.; Morales, Christina; Arunleung, Phacharee; Gonzalez, Andreina Urrutia; Conston, Jacob; Liu, Stephenie; Davis, Ryan; Brown, Jeremy; et al. (Frontiers in Public Health, 2025)
California’s SARS-CoV-2 genomic surveillance program (California COVIDNet) developed whole genomic sequencing (WGS) capability from positive COVID-19 antigen tests to maintain genomic surveillance from public test sites. Over 4-months, COVIDNet sourced specimens from positive COVID-19 antigen tests from 142 California public test sites in 43 counties. Successful WGS was defined as at least 83% reference coverage with a minimum 20x genomic read depth. There were 14,088 SARS-CoV-2 genomes obtained from positive antigen tests with a success rate of 92.9%. The program generated 13.9% of SARS-CoV-2 sequences in California and 2.7% of sequences in the US during the program operation period. In one rural region, 69% of all SARS-CoV-2 sequences were generated by the program. California successfully transitioned SARS-CoV-2 WGS on a statewide scale to specimens sourced from positive antigen tests. Community-based testing coupled with a comprehensive genomic surveillance program provides a statewide strategy applicable to other pathogens of public health significance.